VIJAY TENDULKAR ‘S THEMATIC CONCERNS - Pramod Thakur (International Journal of Multidisciplinary Research and Studies, 2021)
Young Vijay was inspired to begin writing as a result of the literary atmosphere that existed in his household. At the age of six, he composed his first narrative. After spending his childhood seeing western plays, he became motivated to compose plays of his own. He wrote, directed, and appeared in his very first play when he was just eleven years old. After dropping out of school at the age of 14, he joined the Indian Freedom Movement and became active in the cause. The latter caused him to become estranged from his family as well as his pals. Work became his release after that, despite the fact that the majority of his early writing was of a more personal character and was written with the intention of being published. Writing for newspapers was where Tendulkar's professional life first started. Tendulkar's works swiftly altered the plot of contemporary Marathi theatre in the 1950s and 1960s, when experimental performances were staged by theatrical companies such as Rangayan. Vijay began his professional life as a journalist and then rose through the ranks to become the head of the Sangeet Nataka Academy. He authored thirty full-length plays in Marathi, ten of which were translated into English. He also wrote plays in other Indian languages. The ideas of power, aggression, and inequality between the sexes are presented in a variety of ways throughout all of these plays. Both Silence! The Court Is In Session and Kamala, two of his plays, deal with the topic of gender-based discrimination in some form or another. The play Sakharam Binder is an examination of the violent nature of humans.